Enhancing ophthalmology education through a mobile flipped classroom: a new teaching method - Maryam Yadgari; Masomeh Kalantarion; Mohammad-Mehdi Sadoughi; Soleiman Ahmady; Mohammad-Hasan Shahriari (BMC Research Notes)
Abstract Objective Glaucoma is a major cause of irreversible blindness globally. Optical coherence tomography (OCT) aids early glaucoma diagnosis. Interpreting OCT scans requires familiarity with the technology and image analysis. This study aimed to evaluate the effects of a mobile flipped classroom model on learning outcomes and satisfaction for teaching optical coherence tomography (OCT) interpretation skills in glaucoma. Results In this quasi-experimental pre/post-test study, a total of 22 ophthalmology residents participated in a 4-session mobile flipped classroom educational intervention (90 min/session) and were assessed on OCT interpretation. Learning was measured via pre/post-tests designed by a panel. Satisfaction was assessed using a validated questionnaire. Mean participant age was 29.42 (± 2.09) years. Compared to pre-intervention, post-test scores showed significant improvement after the mobile flipped classroom (p < 0.001). Mean satisfaction score was 74.05 (± 16.09), denoting high satisfaction. Implementing a mobile flipped classroom significantly improved OCT interpretation skills and was associated with high satisfaction ratings among ophthalmology residents. This model shows promise for enhancing clinical knowledge in graduate medical education.